An Empirical Model of the Ionospheric Sporadic E Layer Based on GNSS Radio Occultation Data. Issue 8 (8th August 2022) - Yu, Bingkun; Xue, Xianghui; Scott, Christopher J.; Yue, Xinan; Dou, Xiankang
Abstract: The intense plasma irregularities within the ionospheric sporadic E ( E s ) layers at 90–130 km altitude have a significant impact on radio communications and navigation systems. As a result, the modeling of the E s layer is very important for the accuracy, reliability, and further applications of modern real‐time global navigation satellite system precise point positioning. In this study, we have constructed an empirical model of the E s layer using the multivariable nonlinear least‐squares‐fitting method, based on the S4max from Constellation Observing System for Meteorology, Ionosphere, and Climate satellite radio occultation measurements in the period 2006–2014. The model can describe the climatology of the intensity of E s layers as a function of altitude, latitude, longitude, universal time, and day of year. To validate the model, the outputs of the model were compared with ionosonde data. The correlation coefficients of the hourly f o Es and the daily maximum f o Es between the ground‐based ionosonde observations and model outputs at Beijing are 0.52 and 0.68, respectively. The model can give a global climatology of the intensity of E s layers and the seasonal variations of E s layers, although the E s layers during the summer are highly variable and difficult to accurately predict. The outputs of the model can be implemented in comprehensive models for a description of the climatology of E s layers and provide relatively accurate information about the global variation of E s layers. Plain Language Summary: Sporadic E ( E s ) layers are unusual clouds of intense ionization in the upper atmosphere. The E s layer causes anomalous long‐distance propagation of radio waves; thus, it can have a significant impact on wireless radio communications. The effects of the E s layer on the global positioning system/global navigation satellite system (GNSS) radio occultation (RO) receivers can be used to study the global occurrence and intensity of E s layers. Even though the formation mechanism of the midlatitude E s layer is well‐known and related to the ion vertical drift, its prediction is hard due to a large uncertainty in neutral winds from numerical models. In this study, we have constructed an empirical model of the E s layer based on the maximum value of the amplitude scintillation S4 index (S4max) from GNSS RO observations during the period 2006–2014. A function is fitted to the S4max data to provide the empirical model outputs continuously in altitude, latitude, longitude, time of day, and day of year. The model performance is validated by ground‐based ionosonde data. This model can be used for applications requiring global climatology of E s layers or requiring the climatology of the E s layer at some location far from the observing ionosondes. Key Points: An empirical model of the E s layer is constructed, based on S4max data retrieved from Constellation Observing System for Meteorology, Ionosphere, and Climate satellite occultation measurements The model can provide the climatology of the intensity of E s layers as a function of altitude, latitude, longitude, universal time, and day of year The correlation coefficients of hourly f o Es and daily maximum f o Es between observations and model are 0.52 and 0.68, respectively